Detection of Parvovirus B19 DNA in pregnant Sudanese women attending The Military hospital using Nested PCR technique : Detection of Parvovirus B19 DNA in pregnant Sudanese women - Abdelkabeer, Tagwa Hafiz; Mohammed, Nusaiba Elhadi; Khider, Jala Suliman; Yassin, Mustafa Eltigani; Idris, Alkhair Abd Almahmoud (AL-Kindy College Medical Journal, 2022)
Background: Parvovirus B19 is a human pathogenic virus associated with a wide range of clinical conditions. During pregnancy congenital infection with parvovirus B19 can be associated with poor outcome, including miscarriage, fetal anemia and non-immune hydrops. Objective: The study aimed to determine the prevalenceof Parvovirus B19 DNA in pregnant women attending the Military hospital in Khartoum, demonstrating the association between the virus and poor pregnancy outcomes. Subjects and methods: This study was a cross sectional study, testing pregnant Sudanese women whole blood samples (n= 97) for the presence of Parvovirus B19 DNA using nested PCR technique. Result: Two samples were found positive for Parvovirus B19 DNA out of the total number of samples screened. Conclusions: The prevalence of Parvovirus B19 DNA among pregnant women attending the Military hospital was 2.1%.